2008
DOI: 10.1080/10543400802071378
|View full text |Cite
|
Sign up to set email alerts
|

On Statistical Evaluation of the Linearity in Assay Validation

Abstract: Linearity is one of the most important characteristics for evaluation of the accuracy in assay validation. The current statistical method for evaluation of the linearity recommended by the Clinical Laboratory Standard Institute (CLSI) guideline EP6-A is reviewed. The method directly compares the point estimates with the pre-specified allowable limit and completely ignores the sampling error of the point estimates. An alternative method for evaluation of linearity, proposed by Kroll et al. (2000), considers the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…However, Hsieh and Liu [2] pointed out that the formulation of hypothesis given in Equation (3) is not appropriate for linearity validation and they suggested that the hypothesis of proving the linearity formulated as the alternative hypothesis as follows:…”
Section: Experiments Designmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Hsieh and Liu [2] pointed out that the formulation of hypothesis given in Equation (3) is not appropriate for linearity validation and they suggested that the hypothesis of proving the linearity formulated as the alternative hypothesis as follows:…”
Section: Experiments Designmentioning
confidence: 99%
“…Throughout the simulation, mean concentration m is assumed to be 4 and the allowable margin of linearity based on ADL, u 0 , is specified 0.05 as recommended by Kroll et al [1]. From the relationship that SSDL ¼ L(mu) 2 , it follows that the margin for SSDL for 5 and 7 concentrations are 0.2 and 0.28, respectively. In addition, standard deviation of normal random error is specified as 0.1 and 0.2.…”
Section: Simulation Studymentioning
confidence: 99%
See 3 more Smart Citations